Development and application of oncolytic viruses as the nemesis of tumor cells - Zhu, Xiao; Fan, Chenyang; Xiong, Zhuolong; Chen, Mingwei; Li, Zesong; Tao, Tao; Liu, Xiuqing (Frontiers in Microbiology, 2023)
Viruses and tumors are two things that are harmful to humans, but what happens when a virus meets a tumor? There is a consensus among cancer patients all over the world that only surgical resection, chemotherapy, radiotherapy, and other means can fight against cancer. However, with the innovation and development of biomedical technology, tumor biotherapy (immunotherapy, molecular targeted therapy, gene therapy, oncolytic virus therapy, etc.) has become another means of treatment for malignant tumors. The oncolytic virus has many anti-tumor characteristics, such as directly splitting tumor cells, activating the anti-tumor immune response, and improving the tumor microenvironment. Compared with traditional immunotherapy, oncolytic virus thera-py has the advantages of high killing efficiency, good targeting, and small side effects. Since the 19th century, oncolytic virus (OV) therapy has officially entered the field of tumor treatment as a new method, but the effect is not ideal, so it has not been widely used. Since the U.S. Food and Drug Administration (FDA) approved the first OV therapy drug T-VEC to be launched in 2015, OV has received more and more attention. In recent years, oncolytic virus therapy has had a bet-ter and better application prospect and is a major research hotspot in the field of cancer treatment. This article reviews the development, classification, and research progress of oncolytic viruses, as well as their mechanisms of action, therapeutic methods, and routes of administration.